2014
DOI: 10.1111/jcpe.12220
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of soft tissue augmentation around dental implants and in partially edentulous areas: a systematic review

Abstract: Aim To review the dental literature in terms of efficacy of soft tissue augmentation procedures around dental implants and in partially edentulous sites. Methods A Medline search was performed for human studies augmenting keratinized mucosa (KM) and soft tissue volume around implants and in partially edentulous areas. Due to heterogeneity in between the studies, no meta‐analyses could be performed. Results Nine (KM) and eleven (volume) studies met the inclusion criteria. An apically positioned flap/vestibulopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
250
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(287 citation statements)
references
References 67 publications
6
250
0
9
Order By: Relevance
“…Especially in highly demanding esthetic areas this may not lead to an appealing result. In order to gain additional volume a soft tissue augmentation procedure may be the therapy of choice [6]. Soft tissue augmentation procedures following implant placement are widely performed surgical interventions preceding abutment connection mainly and are reported to account for up to 43% of the final volume based on clinical data [7].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in highly demanding esthetic areas this may not lead to an appealing result. In order to gain additional volume a soft tissue augmentation procedure may be the therapy of choice [6]. Soft tissue augmentation procedures following implant placement are widely performed surgical interventions preceding abutment connection mainly and are reported to account for up to 43% of the final volume based on clinical data [7].…”
Section: Introductionmentioning
confidence: 99%
“…22 The use of coronally advanced flaps and connective tissue grafts for treating gingival recessions can sometimes jeopardize the esthetic appearance of the treatment sites in both color and tissue thickness as compared to the adjacent soft tissues. 23 Thoma et al 24 conducted a systematic literature review and reported that the combination of an apically positioned flap/vestibuloplasty and soft tissue augmentation using a free gingival graft, subepithelial connective tissue graft or collagen matrix resulted in a 1.4-3.3 mm increase of keratinized tissue. Overall, connective tissue augmentation resulted in the best volume of soft tissue gains at implant and partially edentulous sites, and a combination of better papilla fill and higher marginal mucosal levels as compared to non-grafted sites around immediately placed dental implants.…”
mentioning
confidence: 99%
“…Overall, connective tissue augmentation resulted in the best volume of soft tissue gains at implant and partially edentulous sites, and a combination of better papilla fill and higher marginal mucosal levels as compared to non-grafted sites around immediately placed dental implants. 24 This retrospective clinical case series reports on the findings of an innovative surgical technique designed to restore hard tissue profiles and increase keratinized gingiva around dental implants in the esthetic zone.…”
mentioning
confidence: 99%
“…According to recent systematic reviews, the use of autogenous tissue harvested from the retromolar or palatal area is considered to be the gold standard around teeth and dental implants in partially edentulous patients (Thoma et al, 2014, Thoma et al, 2009, Levine et al, 2014, Cairo et al, 2014. Whereas these transplants and techniques are well documented, disadvantages are often reported, mostly due to the morbidity associated with the harvesting procedure and the respective second surgical site (Griffin et al, 2006, Wessel and Tatakis, 2008, Harris et al, 2005.…”
mentioning
confidence: 99%